Cadmium in cacao: what we know about mitigation practices: Second Clima-LoCa briefing note on cadmium in cacao - Vanderschueren, Ruth; Pulleman, Mirjam Margreet (2021)
Clima-LoCa is a regional project led by the Alliance of Bioversity International and the International Center for Tropical Agriculture (CIAT), implemented with research partners from Latin America and Europe and funded by the European Commission. This project addresses important challenges related to the resilience, competitiveness, and inclusiveness of the growing cacao sector. Here, resilience refers to the capacity of smallholder producers, and other value chain actors, to mitigate the negative impacts of new EU food safety regulations on cadmium in cacao, and of climate change. This second Clima-LoCa briefing note on cadmium in cacao examines some of the commonly asked questions regarding cadmium in cacao in a science-backed manner and to iron out some persisting misconceptions. The current briefing note discusses the scientific evidence to date on strategies that farmers can apply to diminish cadmium concentration in cacao beans. These mitigation strategies can be divided into three main categories: soil amendments, cultivar selection, and postharvest strategies. Field research to evaluate the effectiveness of amendments in different soil types and agroecological conditions is critical, and must pay attention to implications for farmer income and acceptance.